2019
DOI: 10.3390/su11102768
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Vulnerability of Typhoon in Residential Facilities: Focusing on Typhoon Maemi in South Korea

Abstract: Typhoons cause severe monetary damage globally. Many global insurance companies and public agencies are currently developing and utilizing windstorm risk estimation models to calculate the level of risk and set up strategies for avoiding, mitigating, and relocating those economic risks. Hence, the usage and accuracy of the windstorm risk estimation model is becoming increasingly significant, and reflecting local vulnerabilities is essential for refined risk assessment. While key risk indicators have been recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The field measurement of the wind characteristics mainly paid attention on the typhoon and mountainous wind fields. As for the typhoons, the researchers examined the mean wind speed profiles and turbulent spectrum in their outer regions (Kim et al 2019a;Tao and Wang 2019b;Zhao et al 2019c). Based on these studies, the wind field in the outer region of typhoon can be roughly summarized as: (a) the wind characteristics in the outer region of typhoon are very similar to those of non-typhoon wind; (b) their probability density function of fluctuating wind speed almost follows a Gaussian distribution; (c) the power spectrum can be expressed by a Von Kármán-type.…”
Section: Wind Resistance Of Bridgementioning
confidence: 99%
“…The field measurement of the wind characteristics mainly paid attention on the typhoon and mountainous wind fields. As for the typhoons, the researchers examined the mean wind speed profiles and turbulent spectrum in their outer regions (Kim et al 2019a;Tao and Wang 2019b;Zhao et al 2019c). Based on these studies, the wind field in the outer region of typhoon can be roughly summarized as: (a) the wind characteristics in the outer region of typhoon are very similar to those of non-typhoon wind; (b) their probability density function of fluctuating wind speed almost follows a Gaussian distribution; (c) the power spectrum can be expressed by a Von Kármán-type.…”
Section: Wind Resistance Of Bridgementioning
confidence: 99%
“…Economic growth in South Korea is underpinned by railways and highway systems, which pass through many tunnels due to the complicated geomorphological and geological settings. Far from mitigating their inherent disadvantages, including but not limited to vulnerability to collapse, landslides, and flooding during construction [8][9][10], increased demand for tunnels has merely proliferated risk and uncertainty [11]. Insurance Statistics Information Services [12] revealed that insured losses during tunnel construction in South Korea over the period 2005-2016 totaled US$8.77 million.…”
Section: Research Background and Objectivementioning
confidence: 99%
“…In addition to construction-industry and governmental efforts to mitigate the number and severity of construction accidents, the insurance industry itself has developed risk-assessment models for potential construction project-related losses [11]. However, those in-house models are limited in their usefulness, since they are typically derived from narrow ranges of projects and/or particular regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many leading companies involved in construction projects make a great deal of effort to estimate the possible losses during construction work. In particular, insurance and re-insurance companies have developed their own loss assessment models to predict and prepare for the potential losses [15]. These loss estimation models in fact help the insurers and their customers to understand and estimate the potential risks in construction projects.…”
Section: Loss From Third-party Damagementioning
confidence: 99%